Research papers Conformational flexibility of EptA driven by an interdomain helix provides insights for enzyme– substrate recognition. (2021) - Anandan, Anandhi; Dunstan, Nicholas W.; Ryan, Timothy M.; Mertens, Haydyn D. T.; Lim, Katherine Y. L.; Evans, Genevieve L.; Kahlerd, Charlene M.; Vrielink, Alice
No abstract available